Late-Onset Carnitine–Acylcarnitine Translocase Deficiency With SLC25A20 c.199-10T>G Variation: Case Report and Pathologic Analysis of Liver Biopsy - Chen, Min; Cai, Yao; Li, Sitao; Xiong, Hui; Liu, Mengxian; Ma, Fei; Xiao, Xin; Hao, Hu (Frontiers in Pediatrics, 2020)
Introduction: Carnitine–acylcarnitine translocase deficiency (CACTD) is a rare and life-threatening autosomal recessive disorder of mitochondrial fatty acid oxidation caused by variation of the Solute carrier family 25 member 20 (SLC25A20) gene. Carnitine–acylcarnitine translocase is one of the crucial transport proteins in the oxidation process of mitochondrial fatty acids. In Asia, the c.199-10T>G splice site variation is the most frequently reported variant of SLC25A20. Patients with CACTD with c.199-10T>G variation usually present with a severe clinical phenotype. Materials and Methods: Herein, we report a neonatal case of late-onset CACTD in mainland China. Symptoms emerged 61 days after birth; the patient presented with a severe metabolic crisis, and her clinical condition rapidly deteriorated, and she died of respiratory insufficiency and cardiac arrest at 61 days. We present the clinical and biochemical features of this patient and briefly review previously reported CACTD cases with c.199-10T>G variation. Results: Acylcarnitine profiling by tandem mass spectrometry and high-throughput sequencing revealed that our patient was homozygous for the c.199-10T>G variation, confirming the diagnosis of CACTD. Histopathologic analysis of the liver by Prussian blue staining showed focal iron deposition in hepatocytes, and electron microscopy analysis revealed a large number of lipid droplet vacuoles in diffusely distributed hepatocytes. Conclusion: The development of CACTD in our patient 61 days after birth is the latest reported onset for CACTD with SLC25A20 c.199-10T>G variation. Early recognition of symptoms and timely and appropriate treatment are critical for improving the outcome of this highly lethal disorder. Death from late-onset CACTD may be caused by the accumulation of long-chain fatty acids as well as iron deposition in the heart leading to heart failure.